(untitled) (African Human Mobility Review, 2021)
The main objective of this research article, is to assess the effect of socio-economic and environmental determinants on the healthy aging status amongst internally displaced migrants and non-migrants nestled within the environmentally stressed regions of Northeastern Nigeria. Methodologically the study utilized secondary data from the Nigerian IDP Survey 2018 (Location-Northeastern States; n-1293 adults aged â‰¥50; male n-63.1%, female n-36.9%) using a multi-stage stratified random sample. Varied statistical techniques such as cross-tabulation and binary logistic regression were used to analyze the dataset. The study results show a high mean prevalence of old-age disability within the study area, irrespective of migration status in Northeastern Nigeria. Secondly, socio-economic and environmental determinants were robust predictors of later-life health outcomes. In addition, the regression revealed that concomitant factors such as age, gender and sanitation have a negative effect on older adult wellness and well-being. Meanwhile, the migration status of internally displaced persons (IDPs), although in most cases forced, significantly improves the odds of aging healthily. Conclusively, the quality of life of the older adults, irrespective of migration status, is poorly impacted by diminishing familial supports, social exclusion, non-existent social security program and non-existence of healthcare infrastructure. Based on the study results, we recommend that the proposed Economic Community of West African States (ECOWAS) Sahelian â€œGreen beltâ€ afforestation project targeted, especially to areas around the Chad basin be fully implemented, as this project will help mediate the perennial conflicts between the herdsmen and farming communities.